Single nucleotide polymorphisms in AGTR1, TFAP2B, and TRAF1 are not associated with the incidence of patent ductus arteriosus in Japanese preterm infants - Kawase, Koya; Sugiura, Tokio; Nagaya, Yoshiaki; Yamada, Takaharu; Sugimoto, Mari; Ito, Koichi; Togawa, Takao; Nagasaki, Rika; Kato, Takenori; Kouwaki, Masanori; Koyama, Norihisa; Saitoh, Shinji (Pediatrics international, 2016)
Background Persistent patent ductus arteriosus (PDA) is a frequent complication in preterm infants. Single nucleotide polymorphisms (SNP) in several genes, including angiotensin II receptor, type 1 (AGTR1), transcription factor AP‐2 beta (TFAP2B) and tumor necrosis factor receptor‐associated factor 1 (TRAF1), have been reported to be associated with PDA in preterm infants. The aim of this study was to evaluate the relationships between PDA in preterm infants and polymorphisms in AGTR1, TFAP2B and TRAF1 in the Japanese population. Methods The subjects consisted of 107 preterm infants with gestational age <32 weeks. Extremely low‐birthweight infants were treated with prophylactic indomethacin during the first 24 h after birth. Five SNP, namely, rs5186 in AGTR1, rs987237 and rs6930924 in TFAP2B, and rs1056567 and rs10985070 in TRAF1, were genotyped using TaqMan SNP genotyping assays. Results There were no significant differences in the distributions of the genotypes and allele frequencies of all studied SNP between the PDA group (n = 46) and the non‐PDA group (n = 61). Conclusions There were no significant associations between the studied SNP and the incidence of PDA in Japanese preterm infants. These SNP may not be clinically important predisposing factors for PDA in Japanese preterm infants.